2020
DOI: 10.1155/2020/2094625
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic Organizing Pneumonia with a Rare Radiographic Presentation of a Diffuse Micronodular Pattern Mimicking Miliary Lung Infiltration: A Case Report and Review of the Literature

Abstract: We reported a case of cryptogenic organizing pneumonia (COP) presenting with an unusual diffuse micronodular pattern (DMP) mimicking miliary lung infiltration. The patient is a 66-year-old man with a past medical history of diabetes mellitus type 2 and hyperlipidemia who presented with progressive dyspnea associated with significant weight loss and night sweats for 2 weeks. Upon admission, the patient’s clinical condition rapidly progressed to respiratory failure requiring mechanical ventilation. Initial Chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, the prevalence of a micronodular pattern of OP (MNOP) on radiological series is estimated to range from 10% to 24%; 4 however, the prevalence of a diffuse pattern in the total lung field of MNOP is rare. 4,5 CT pattern resembling HP has occasionally been observed in patients with immune checkpoint inhibitor (ICI)-induced pneumonia and described as centrilobular nodules, Copyright © 2020 by the American Thoracic Society bronchiolitis-like appearance, and tree-in-bud micronodularity; 6 however, the manifestation of diffuse pattern in the total lung fields of patients with ICI-induced pneumonia is rare. To the best of our knowledge, histopathological study of ICI-induced pneumonia with HP-like CT pattern has not been reported.…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prevalence of a micronodular pattern of OP (MNOP) on radiological series is estimated to range from 10% to 24%; 4 however, the prevalence of a diffuse pattern in the total lung field of MNOP is rare. 4,5 CT pattern resembling HP has occasionally been observed in patients with immune checkpoint inhibitor (ICI)-induced pneumonia and described as centrilobular nodules, Copyright © 2020 by the American Thoracic Society bronchiolitis-like appearance, and tree-in-bud micronodularity; 6 however, the manifestation of diffuse pattern in the total lung fields of patients with ICI-induced pneumonia is rare. To the best of our knowledge, histopathological study of ICI-induced pneumonia with HP-like CT pattern has not been reported.…”
Section: To the Editorsmentioning
confidence: 99%
“…If these features are not detected, a surgical lung biopsy should be considered; however, small biopsy specimens are sufficient for diagnosis. In addition, the prevalence of a micronodular pattern of OP on radiological series is estimated to range from 10% to 24% ( 4 ); however, the prevalence of a diffuse pattern in the total lung field of micronodular pattern of OP is rare ( 4 , 5 ).…”
mentioning
confidence: 99%
“…Various metastatic cancers and other neoplastic processes are known causes of miliary disease [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Several interstitial lung diseases can present atypically with a miliary pattern, such as sarcoidosis [21], pulmonary alveolar microlithiasis [22], various pneumoconioses [23], hypersensitivity pneumonitis [24], lipoid pneumonia [25], vaping-associated lung injury [26], drug-induced pneumonitis [27], and organizing pneumonia [28]. Miscellaneous causes of miliary disease include multifocal micronodular pneumocyte hyperplasia [29] and pulmonary hemosiderosis due to mitral stenosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…OP, cryptogenic or secondary, is a clinicopathological entity characterized by granulation tissue plugs in the lumen of small airways, alveolar ducts, and alveoli. An unusual radiological presentation corresponding to diffuse micronodular pattern mimicking miliary lung infiltration has been reported, and the prevalence of this micronodular pattern of OP (MNOP) in radiological series is estimated to range from 10% to 24% ( 2 , 3 ). The typical MNOP on CT imaging is widespread lung micronodules without diffuse ground-glass opacities, airspace consolidation, or cavitation.…”
mentioning
confidence: 99%